Towards the design of sports compression garments with controlled pressure - Brubacher, K. (Manchester Metropolitan University, 2018)
Sports compression garments (SCGs) are skin-tight, elastic garments that are designed to be smaller than the wearer`s body to apply pressure to the underlying body. This is claimed to improve performance, shorten recovery and prevent injuries. The level of pressure applied by SCGs is affected by a complex interaction of body dimensions, garment characteristics and fabric properties. With most existing research on SCGs drawn from medical or sports science fields, studies frequently neglect considerations of users and the way SCGs behave on the body. Consequently, the SCG-body-relationship is not well understood and the pressures applied by commercial SCGs vary widely. This research set out to enhance theoretical and practical knowledge on the design of SCGs by defining a framework for the design of SCGs with controlled pressure. To achieve this, user experiences with SCGs were obtained through an online survey and wearer trials and the designs and pressure distributions of commercial SCGs were analysed. The research further assessed the feasibility of using the built-in pressure map of the commercial 3D CAD software Optitex PDS 11 to predict pressures applied by SCGs. Findings from the online survey revealed that respondents were overwhelmingly satisfied with commercial SGCs and that they wore SCGs mainly for their recovery-enhancing rather than performance-enhancing properties. Wearer trials with 33 physically active females in SCGs were conducted to capture 3D scans of their bodies and measure the pressure applied by commercial SCGs. The wearer trials indicated that, despite high levels of user satisfaction identified by the online survey, compression levels varied widely across pressure measurement locations and across individuals. This suggests a strong perceptual effect of SCGs. It was concluded that variations in pressure levels were likely to be associated with variations in fit and fabric tension caused by deficiencies in the applied sizing system. The commercial SCGs under investigation were deconstructed, re-engineered and virtually fitted to a set of remodelled body avatars of 15 wearer trial participants. Virtual pressure measurements were compared to in vivo measurements. Findings highlighted problems with the accurate simulation of technical garment properties. It was concluded that 3D CAD virtual fit technology is currently limited to the visual representation of garments for marketing and sales purposes, but is not useful for technical product development or pressure prediction. The findings were synthesised and conceptual design principles and a usercentred design framework were defined leading to the development of a model that incorporates a design process, user needs and technical product requirements: the SCG Design Model. By applying a novel inductive interdisciplinary methodological approach, this work has provided a different perspective to the research on SCGs. This approach has created new knowledge and tools for the design of SCGs and opened up new areas of research. This research has the potential to improve SCGs by, on the one hand, enhancing the theoretical and empirical knowledge base, which is expected to lead to more holistic and better-informed research on SCGs and, on the other hand, facilitating the design of SCGs with controlled pressure in practice.